2021
DOI: 10.3389/fonc.2021.579286
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: Biochemistry and Biology in Cancers

Abstract: The challenge of eradicating cancer is that cancer cells possess diverse mechanisms to protect themselves from clinical strategies. Recently, ferroptosis has been shown to exhibit appreciable anti-tumor activity that could be harnessed for cancer therapy in the future. Ferroptosis is an iron-dependent form of regulated cell death that is characterized by the oxidization of polyunsaturated fatty acids (PUFAs) and accumulation of lipid peroxides. Ferroptosis has been closely correlated with numerous biological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 210 publications
1
33
0
Order By: Relevance
“…Recent studies have demonstrated that BAP1 is also involved in several aspects of cellular metabolism, including ferroptosis [26], a recently identified form of regulated cell death that is induced by metabolic stress from cystine reduction and increased reactive oxygen species [27][28][29]. Epidemiological evidence suggests that high dietary iron intake increases the risk of several cancer types including HCC [30], and ferroptosis has been implicated in the development and therapeutic responses of various types of tumors [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that BAP1 is also involved in several aspects of cellular metabolism, including ferroptosis [26], a recently identified form of regulated cell death that is induced by metabolic stress from cystine reduction and increased reactive oxygen species [27][28][29]. Epidemiological evidence suggests that high dietary iron intake increases the risk of several cancer types including HCC [30], and ferroptosis has been implicated in the development and therapeutic responses of various types of tumors [31].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-g derived from immunotherapy-activated CD8 + T cells synergizing with radiotherapy-activated ataxia-telangiectasia mutated (ATM) suppresses SLC7A11, to induce cystine uptake, enhance tumor lipid oxidation and ferroptosis in human fibrosarcoma and melanoma cells (232). Notably, as we and others previously showed that that ferroptosis inducers target tumor stem cells to inhibit tumor proliferation and reduce metastasis (205,233,234). Several US Food and Drug Administration (FDA)-approved drugs have been shown to induce ferroptosis in tumor cells in preclinical models, but the clinical utility of these ferroptosis inducers require further investigation (2).…”
Section: Ferroptosis Inducersmentioning
confidence: 99%
“…Indeed, the activity of many epigenetic enzymes, including JmjC-domain-containing histone demethylases (JHDMs) and ten-eleven translocation (TET) DNA demethylases, is highly dependent on the availability of iron [29][30][31]. Similarly, hydroxyl radicals, produced during Fe 2+ dependent Haber-Weiss reactions taking place in ferroptotic cells [32], can produce methyl radicals and cause non-enzymatic methylation of cytosine and guanidine residues in the DNA and directly impact methylome changes [33]. Finally, inhibition of cystine import by ferroptosis inducer erastin triggers the activation of the transsulfuration pathway [34], and might limit the availability of the methyl donors required for DNA and histone methylation [35,36].…”
Section: Introductionmentioning
confidence: 99%